Reading, writing and cultivating - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
Reading, writing and cultivating : a resource book for post-literacy trainers based on experiences in Senegal by Juliet Millican 92pp ISBN 90 6443 010 1 Available from CTA.